Presence of Fusarium mycotoxins in feedstuffs and cow milk sampled from Croatian farms during 2015 - Jelka Pleadin; Ana Vulić; Manuela Zadravec; Tina Lešić; Miroslav Benić; Vesna Jaki Tkalec; Nada Vahčić (Mljekarstvo)
Mycotoxins may contaminate food of animal origin due to the carry-over effect and represent a potential risk to human health. The problem of Fusarium mycotoxin contamination becomes an issue especially during rainy years characterised by substantial temperature changes. The aim of this study was to investigate into the level of Fusarium mycotoxins zearalenone (ZEN), deoxynivalenol (DON) and fumonisins (FUM) in maize silage (n=21), concentrated dairy cattle feeds (n=56) and cow milk samples (n=105), taken during 2015 from households located in four Croatian regions. The presence of mycotoxins was determined using validated ELISA methods. A high level of feedstuffs’ contamination was evidenced, especially with ZEN, with values higher than recommended observed in 9.5 % of maize silage samples. Fourteen point three percent (14.3 %) of milk samples were DON positive, with the toxin concentrations ranging from 5.4 to 67.3 μg/L. ZEN was determined in 94.3 % of milk samples, ranging from 0.3 to 88.6 μg/L. FUM were not detected in any of the analysed milk samples. Given the tolerable daily intakes (TDIs) defined for these mycotoxins, human health risks arising from the consumption of cow milk can generally be considered low, even in times characterised by weather conditions that facilitate the production of Fusarium mycotoxins in cereals subsequently used as dairy cattle feed. The exception represents particular milk samples in which high ZEN concentrations were found.